Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil Dan Menengah - Milatul Izza (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2021)
ABSTRACK This research to determine whether the theory business entities has been applied and whether it has carried out financial reporting in accordance with the SAK EMKM at the UMKM Warung Sembako Mama Lita. This research is a qualitative with descriptive approach. With type of primary data, the method of collection is interviews and field observations. The results obtained show that the UMKM Warung Sembako Mama Lita have not applied business entity theory and have not even carried out financial reporting in accordance with SAK EMKM. The reason the two things above have not been stated is because business actors do not understand accounting at all. So in this study, the next researcher directs business actors to apply business entity theory and also assists in the process of preparing and presenting financial statements accordance with SAK EMKM.